C12E7-DPPC mixed systems studied by pyrene fluorescence emission - Rei, M. Céu (2004)
"Trends in colloid and interface science XVI : [the fifteenth meeting of the European Colloid and Interface Society (ECIS) was held in Coimbra from 16th to 21st September 2001] "